1993
DOI: 10.3109/09540269309028296
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bulimia Nervosa

Abstract: The treatment for bulimia nervosa is considered under three broad categories: psychological, pharmacological and combination therapies. It is suggested that there is not one treatment which will benefit allpatients and that a stepped care aproach to treatment allows a rational application of current knowledge. One possible programme of stepped care is outlined, which allows the pragmatic application of current therapeutic techniques within a structured framework.Int Rev Psychiatry Downloaded from informahealth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Surprisingly, descriptions often do not include information about dropping out (Doyle, 1995;Fairburn, 1996), even though levels of engagement would seem to be an important consideration. An exception is a paper reviewing treatments and presenting a stepped treatment programme which incorporates interventions to reduce dropping out (Tiller et al, 1993); however, rates are not specified.…”
Section: Bulimia Nervosamentioning
confidence: 99%
“…Surprisingly, descriptions often do not include information about dropping out (Doyle, 1995;Fairburn, 1996), even though levels of engagement would seem to be an important consideration. An exception is a paper reviewing treatments and presenting a stepped treatment programme which incorporates interventions to reduce dropping out (Tiller et al, 1993); however, rates are not specified.…”
Section: Bulimia Nervosamentioning
confidence: 99%
“…An alternative approach to clinical algorithms of care is to have treatment arranged in a series of steps of graded intensity. A sequential model was recommended in the Royal College of Psychiatrists' Report in 1992 and several alternative models have been described, all of which suggest that a series of treatments increasing in intensity are offered in a stepped fashion (Agras, 1993;Fairburn and Peveler, 1990;Fairburn et al, 1992;Garner et al, 1986;Garner and Needleman, 1997;Tiller et al, 1993). The advantage of such an approach is that it does not waste resources in that those who respond to a minimal intervention are`®ltered out' at the earliest possible stage.…”
Section: Providing a Servicementioning
confidence: 99%
“…Much attention has been given to the evaluation of treatment for adults with bulimia nervosa. Pharmacological, nutritional and cognitive behavioural therapy have come to dominate research in the field (Freeman, 1991;Tiller et al, 1993). Although significant improvement is claimed in many treatment studies it is becoming clearer that the majority of subjects still have some symptoms on completion of treatment (Mitchell, 1991;Tiller et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological, nutritional and cognitive behavioural therapy have come to dominate research in the field (Freeman, 1991;Tiller et al, 1993). Although significant improvement is claimed in many treatment studies it is becoming clearer that the majority of subjects still have some symptoms on completion of treatment (Mitchell, 1991;Tiller et al, 1993). Recently Fairburn and colleagues ( 1993) have reported that an interpersonal Family therapy f o r bulimia in adolescents 61 form of psychotherapy has long-term outcome results as good as those achieved with cognitive behavioural therapy.…”
Section: Introductionmentioning
confidence: 99%